Moral spillover in carbon offset judgments - Sörqvist, Patrik; MacCutcheon, Douglas; Holmgren, Mattias; Haga, Andreas; Västfjäll, Daniel (Frontiers in Psychology, 2022)
Moral spillover occurs when a morally loaded behavior becomes associated with another source. In the current paper, we addressed whether the moral motive behind causing CO2 emissions spills over on how much people think is needed to compensate for the emissions. Reforestation (planting trees) is a common carbon-offset technique. With this in mind, participants estimated the number of trees needed to compensate for the carbon emissions from vehicles that were travelling with various moral motives. Two experiments revealed that people think larger carbon offsets are needed to compensate for the emissions when the emissions are caused by travelling for immoral reasons, in comparison with when caused by travelling for moral reasons. Hence, moral motives influence people’s judgments of carbon-offset requirements even though these motives have no bearing on what is compensated for. Moreover, the effect was insensitive to individual differences in carbon literacy and gender and to the unit (kilograms or tonnes) by which the CO2 emissions were expressed to the participants. The findings stress the role of emotion in how people perceive carbon offsetting.